Digital Service Quality, Institutional Trust, and Citizen Satisfaction in Indonesian Municipal E-Government Systems - Rina Wulandari Rina Wulandari (Kalam Practica Media, 2025)
Digital transformation in public administration has become a strategic priority for local governments across Southeast Asia. In Indonesia, municipal governments increasingly rely on e-government platforms to deliver administrative services, yet user satisfaction remains inconsistent. This study examines the relationships among digital service quality, citizen trust, and user satisfaction in municipal e-government systems. Drawing upon the DeLone and McLean Information Systems Success Model and trust theory, the research proposes an integrated model in which system quality, information quality, and service responsiveness influence citizen trust and satisfaction. A quantitative survey was conducted involving 428 users of online population administration services across four Indonesian municipalities. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that system quality and service responsiveness significantly affect citizen trust, while information quality shows both direct and indirect effects on satisfaction. Citizen trust partially mediates the relationship between digital service quality and user satisfaction. The structural model explains 72.6% of the variance in satisfaction. The findings contribute to e-government and public management literature by empirically validating a trust-mediated service quality model in a developing country context. Practically, the study provides actionable insights for municipal policymakers seeking to enhance digital governance performance through improved reliability, transparency, and responsiveness.